CURCUMIN IMPROVE RECOMBINANT THERAPEUTIC ANTIBODY PRODUCTION IN CHINESE HAMSTER OVARY (CHO) CELL LINE STRAIN TU1 BY REGULATING THE CELL CYCLE - Nurazizatul Hasanah, Afifah
Therapeutic protein is currently an alternative method in the field of treatment for several diseases, such as cancer, autoimmunity diseases, and genetic disorders. Monoclonal antibody is one of the therapeutic proteins that are commonly used and the market demand is increasing every year. Therefore, an efficient strategy is needed to produce monoclonal antibodies to meet those needs. One strategy that can be done is to do genetic engineering and process engineering on host cells in order to produce large amounts of recombinant antibodies. An example of host cells that can be used to produce recombinant protein are mammalian cell lines, such as Chinese Hamster Ovary (CHO) cell line which is commonly used to facilitate recombinant antibodies using their ability to do post-translational modification that is similar with human. Furthermore, this cell line could be adapted to suspension culture, so that it would be favorable for large-scale production cultures. In this study, CHO cells strain TU1 were used as host cells. This strain originates from the CHO-K1 cell line that has been engineered to produce high amounts of IgG1 monoclonal antibodies. Process engineering is carried out to increase the productivity of protein production in the CHO-TU1 cell line by increasing cell culture’s life span. Addition of natural product can be used as a strategy to overcome it. One of the natural product that can be used is curcumin, a polyphenol compound from the Curcuma longa L. Previous research stated that curcumin can made cells grow slower by holding it in the phase of G1 / S cell cycle on cancer cells. Therefore, the aim of this experiment was to analyze the effect of curcumin on CHO-TU1 cell growth and its correlation with recombinant antibody production (IgG1) in CHO-TU1 cells. In this study, four concentrations of curcumin (5, 10, 15, and 20 ?g / ml) were added to CHO-TU1 cell culture media, respectively. Difference every 24 hours and IgG1 production were analyzed using Sandwich-ELISA. Cell cycle analysis is carried out using Cell Clock Assay (Biocolor) and Real Time q-PCR to several genes involved in the cell cycle, namely ccnd1, ccnb1, and caspase3, while ?-actin was used as control. Sandwich-ELISA results showed that IgG1 production in CHO-TU1 cells that were administrated with 15 ?g / ml of curcumin higher at 120 hours post-administration compared with controls. Observation of cell cycles showing a comparison of 15 ?g / ml curcumin can accelerate CHO cell growth (p <0.05) and hold cells in the G1 / S phase. This is associated RT-qPCR results that shows an increase of 15 ?g / ml addition of curcumin can down-regulate ccnd1 which replaces it in the G1 / S transition phase in the cell cycle. Based on the results of these studies, it can be concluded that administration of curcumin with a concentration of 15 ?g / ml can arrest the CHO-TU1 cell cycle in G1 / S phase and increase IgG1 productivity in these cell lines, thereby curcumin is potential growth supplements for CHO-TU1 cell line to increase its productivity in producing IgG1 recombinant antibodies.